A Systematic Review on Diabetic Retinopathy Classification Using AI Techniques and IoMT - D., Nithiya Priya; Hanifah, Mohamed; K., Ayyappan; A.R., Rajalakshmi (Journal of ISMAC, 2025)
Diabetic retinopathy is a complication in the retina of the eye due to the accumulation of high glucose levels among the Type 1 and Type 2 diabetes patients. It has also been noted that early diagnosis of the diabetic retinopathy helps patients overcome vision loss. The Internet of Medical Things (IoMT) is an emerging technology in the medical field that allows patients to send and receive medical data to hospitals and consult with doctors as needed. IoMT applications in diabetic retinopathy assist not only in early detection but also in diagnosis, enabling patients in the early stages to address vision problems. Therefore, this paper presents a survey of various machine learning, deep learning, combined AI techniques, the role of smartphones and handheld devices, and the application of IoMT in the early detection and diagnosis of diabetic retinopathy to mitigate vision loss in patients.